The influence of content knowledge on teaching and learning in Traditional and Sport Education contexts: an exploratory study. (2nd September 2016) - Iserbyt, Peter; Ward, Phillip; Martens, Jonas
Abstract : Background : Our understanding of the role in which content knowledge (CK) can strengthen instructional models and how that knowledge matters for professional development is limited. It is contended that mere use of an instructional model is insufficient to impact psychomotor learning in meaningful ways. Purpose : This study was conducted to investigate how a teacher's enacted pedagogical content knowledge (PCK) differed as a function of CK and Sport Education (SE), and to investigate the relative contribution of CK and Sport Education on student learning in terms of swimming performance. Methods : Four intact classes comprising 88 secondary school students (age: 16–17 years) were randomly assigned to a Traditional, an Sport Education, a Traditional-CK, and a SE-CK group. All classes were taught by the same teacher during a 10-day unit of instruction in the front crawl. Results : Results showed that the teacher's PCK differed as a function of improved CK. For verbal representations, the amount of cues in the Traditional-CK and SE-CK groups increased about sixfold compared to the Traditional and the SE group. For visual representations, more partially incorrect demonstrations were observed than correct demonstrations in the Traditional and the SE group. More mature and developmentally appropriate tasks were observed in the Traditional-CK and the SE-CK group compared to the Traditional and the SE group. Students in the Traditional-CK and SE-CK groups demonstrated a significant reduction of their amount of strokes on 50 m compared to the Traditional group. A significant interaction effect revealed a larger increase in swimming performance in the CK groups compared to the Traditional and the SE group. Finally, students in the SE group swam significantly more laps than their counterparts in the other groups. Discussion and conclusion : These results show the impact on student learning when CK was added to both Traditional and Sport Education conditions and contribute to the literature for pre- and in-service teachers. The Sport Education model did not contribute to students' swimming performance. Students in the Traditional and the SE group did not get the same quality of instruction as students in the Traditional-CK and SE-CK conditions. The latter groups received content that was presented differently both as a presentation and in terms of the actual task. In short, students in the Traditional and Sport Education conditions experienced the content differently than those in the Traditional-CK and SE-CK conditions. These instructional differences resulted in students in the Traditional-CK and SE-CK conditions improving their swimming performances in terms of technical efficiency and in terms of 50 m times.